Biochemical profiles of patients with COVID-19 during the first and second waves in Ethiopia - Getahun, Habtamu Abebe; Legesse, Assefa; Desta, Diliab; Johar, Ahmed; Bekele, Israel; Angasu, Kebenesa; Hunegnaw, Samuel; Simegnew, Nebiyou; Fekadie, Minale (Frontiers in Immunology, 2024)
Coronavirus disease 2019 (COVID-19) is a highly infectious disease caused by severe acute respiratory syndrome coronavirus 2. Nasopharyngeal swabs (NP swabs) were used for patients with COVID-19 who demonstrated serious clinical symptoms and disturbances in biochemical parameters. The biochemical profiles of these patients remain ambiguous and differ from wave to wave of COVID-19 infections. Herein, we conducted a multicenter retrospective cohort study with 538 patients with COVID-19 at six COVID-19 treatment centers in Ethiopia. Professional data collectors collected the data. Descriptive statistics were used to summarize the data, and independent t-tests and chi-square tests were used to assess the relationships between the continuous and categorical variables across waves, respectively. In total, 240 and 298 patients were included from the first and second waves, respectively. Men and individuals aged 53–69 years were more likely to be infected in each wave. The mean alkaline phosphatase (p < 0.001) and sodium levels (p = 0.035) significantly differed between patients across the two waves of COVID-19; the significant difference in the alkaline phosphatase levels of patients between the two waves was −45.425. All the symptoms of COVID-19 were significantly (p < 0.05) associated with the waves of the pandemic. Patients in both waves had no chronic disease comorbidities. This study showed that the mean alkaline phosphatase and sodium levels differed significantly across the first two waves of the pandemic at six COVID-19 treatment centers in Ethiopia while all clinical symptoms of COVID-19 were associated with the first two waves of the pandemic.